A Highly Compressible and Stretchable Carbon Spring for Smart Vibration and Magnetism Sensors. Issue 39 (13th August 2021) - Gao, Huai‐Ling; Wang, Ze‐Yu; Cui, Chen; Bao, Jia‐Zheng; Zhu, Yin‐Bo; Xia, Jun; Wen, Shao‐Meng; Wu, Heng‐An; Yu, Shu‐Hong
Abstract: Porous carbon materials demonstrate extensive applications for their attractive characteristics. Mechanical flexibility is an essential property guaranteeing their durability. After decades of research efforts, compressive brittleness of porous carbon materials is well resolved. However, reversible stretchability remains challenging to achieve due to the intrinsically weak connections and fragile joints of the porous carbon networks. Herein, it is presented that a porous all‐carbon material achieving both elastic compressibility and stretchability at large strain from −80% to 80% can be obtained when a unique long‐range lamellar multi‐arch microstructure is introduced. Impressively, the porous all‐carbon material can maintain reliable structural robustness and durability under loading condition of cyclic compressing–stretching process, similar to a real metallic spring. The unique performance renders it as a promising platform for making smart vibration and magnetism sensors, even capable of operating at extreme temperatures. Furthermore, this study provides valuable insights for creating highly stretchable and compressible porous materials from other neat inorganic components for diverse applications in future. Abstract : A porous spring‐like all‐carbon material achieving both elastic compressibility and stretchability at large strain from −80% to 80% is obtained when a unique long‐range lamellar multi‐arch microstructure is designed. The excellent mechanical performance combined with the intrinsic advantages of carbon makes it a promising platform for making smart vibration and magnetism sensors that can work at extreme temperatures.